Small is Smarter: Nano MRI Contrast Agents – Advantages and Recent Achievements. Issue 5 (17th December 2015) - Gao, Zhenyu; Ma, Tiancong; Zhao, Enyu; Docter, Dominic; Yang, Wensheng; Stauber, Roland H.; Gao, Mingyuan
Abstract : Many challenges for advanced sensitive and noninvasive clinical diagnostic imaging remain unmatched. In particular, the great potential of magnetic nano‐probes is intensively discussed to further improve the performance of magnetic resonance imaging (MRI), especially for cancer diagnosis. Based on recent achievements, here the concepts of magnetic nanoparticle‐based MRI contrast agents and tumor‐specific imaging probes are critically summarized. Advances in their synthesis, biocompatible chemical and biofunctional surface modifications, and current strategies for further developing them into multimodality imaging probes are discussed. In addition, how engineered versus unintended surface coatings such as protein coronas affect the biocompatibility and performance of MRI nano‐probes is also considered. To stimulate progress in the field, future strategies and relevant challenges that still need to be resolved in the field conclude this review. Abstract : Magnetic nanoparticles hold great potential as contrast agents for magnetic resonance imaging and advanced applications in multimodality imaging and drug carriers for cancer thranostics. To promote the development of this field, state‐of‐the‐art achievements are summarized and fundamental scientific challenges are discussed.